Artificial Intelligence Tools in Academic Article Writing: Is it a Tool or a Co-Author? - Dere, Osman (European Journal of Therapeutics, 2023)
Dear Editors, I have read your editorials on the use of artificial intelligence in academic articles with great attention and enthusiasm [1,2]. In addition, in the comments made to your articles, I reviewed the ethical problems that may arise from the use of artificial intelligence in scientific articles and the contributions that the article will provide in the writing process [3-6]. Although technological developments and advances in artificial intelligence have gained great momentum in recent years, I believe they should be accepted as an accumulation of all humanity. As a matter of fact, in very old sources, there is information that the machines known as robots and automatons at that time were used for entertainment purposes in the centuries before Christ. Furthermore, sophisticated machines, water clocks, and programmable humanoid automatons invented by İsmâil bin er-Rezzâz el-Cezerî in the 12th century, which have an important position in our scientific history, have played a significant role in the development of today’s robot technology and mechanical sciences. Artificial intelligence applications are progressively being employed in agriculture, industry, military activities, health, art, and numerous other disciplines. Today, when we type "artificial intelligence" into the Google Scholar, we get 5,410,000 results, demonstrating how these developments have affected the academic world. As indicated in previous comments, I believe that applications such as ChatGPT in academic writings can be used for grammar corrections and abstract editing. Furthermore, these apps might be employed in the introduction section, where broad information about the topic under investigation is provided in the articles. However, since these applications do not only use academic databases during the literature review, the final version of the article should be evaluated by the relevant author. The primary ethical issue with these practices is that they are unable to accept responsibility in proportion to their authority. As a result, regardless of their contribution to the design of the paper, I think that these apps should not be deemed co-authors. However, it should be noted that these applications were used in the article. In conclusion, I believe that in the not-too-distant future, artificial intelligence applications will make significant contributions to the writing of the article, particularly in academic studies involving quantitative data. We should use these technologies as a tool to contribute more to academic advancement. Kind regards,